Electrical codes, standards, recommended practices and regulations an examination of relevant safety considerations - Alonzo, Robert J. (William Andrew/Elsevier, 2010)
Electrical codes, standards, recommended practices and regulations can be complex subjects, yet are essential in both electrical design and life safety issues. This book demystifies their usage. It is a handbook of codes, standards, recommended practices and regulations in the United States involving electrical safety and design. Many engineers and electrical safety professionals may not be aware of all of those documents and their applicability. This book identifies those documents by category, allowing the ready and easy access to the relevant requirements. Because these documents may be updated on a regular basis, this book was written so that its information is not reliant on the latest edition or release of those codes, standards, recommended practices or regulations. No single document on the market today attempts to not only list the majority of relevant electrical design and safety codes, standards, recommended practices and regulations, but also explain their use and updating cycles. This book, one-stop-information-center for electrical engineers, electrical safety professionals, and designers, does. Covers the codes, standards, recommended practices and regulations in the United States involving electrical safety and design, providing a comprehensive reference for engineers and electrical safety professionals Documents are identified by category, enabling easy access to the relevant requirements Not version-specific; information is not reliant on the latest edition or release of the codes, standards, recommended practices or regulations.
Keywords: Electrical engineering -- Safety measures.; Electrical engineering -- Safety regulations.; Electrical engineering -- Standards.; elektronické knihy; electronic books